A Cross Sectional Study on the Prevalence of Dyslipidemia and Diabetes among Young Adults with Hypertension - Naheed Akhtar, Muntaha Hanif, Shehla Parveen, Javaria Amil, Sheraz Saleem (Pakistan Journal of Medical & Health Sciences, 2022)
In hypertensive patients, lipid disorders (LD) and diabetes mellitus (DM) are related with an amplified jeopardy of cardiovascular issues, which require aggressive treatment and close monitoring. Therefore, this study was held to investigate the pervasiveness of dyslipidemia and diabetes in young patients with hypertension less than forty years of age. Study Design: A cross-sectional study. Place and Duration: In the Medicine department of Jinnah hospital Lahore and DHQ Hospital Mianwali for six-months duration from July 2021 to December 2021. Methods: A total of 150 patients with hypertension under forty years of age, receiving antihypertensive treatment or newly diagnosed with hypertension were enrolled in the study. Blood pressure was measured twice with 30 minutes interval in sitting position on the right arm and average BP was recorded. The fasting blood glucose and lipid profile were evaluated after fasting for 12hrs, and the incidence of diabetes and dyslipidaemia was analyzed from the collected data. All statistical analyses and calculations are determined by SPSS 25.0. Results: Of the 150 enrolled patients, 107 (71.3%) were aged 31-39 and 37 (24.7%) were aged 21-30 and 6(4%) were ≤ 20 of age group. 95 (63.3%) are men and 55 (36.7%) are women. The pervasiveness of pre-diabetes was 46 (30.7%) and diabetes mellitus was 17 (18%). The incidence of dyslipidaemia was 110 (73.3%) with the communal disorder being high triglycerides trailed by low HDL in 82(54.7%) patients. Of high cholesterol, high LDL cholesterol in 19 (12.7%) patients and very high LDL level in 13(8.7%) subjects. Among patients with regarding to HDL cholesterol; low level HDL cholesterol was seen in 82 (54.7%) subjects and 68 (45.3%) patients in acceptable level. Conclusions: A high incidence of pre-diabetes, dyslipidemia and diabetes was noticed in patients with hypertension under 40 years of age.